Equilibrium and kinetics studies of naproxen adsorption onto novel magnetic graphene oxide functionalized with hybrid glycidoxy-amino propyl silane - Mohammad Kazem Mohammadi Nodeh; Narmin Kanani; Elahe Beirak Abadi; Hassan Sereshti; Anahita Barghi; Shahabaldin Rezania; Gholamreza Nabi bidhendi (Environmental Challenges, 2021)
A hybrid silica-gel (3-glycidoxypropyl)trimethoxysilane/(3-aminopropyl)triethoxysilane magnetic graphene oxide (GPTMS/APTMS-MGO) nanocomposite was synthesized and used as an adsorbent for the magnetic removal of naproxen from water samples. The adsorbent was characterized using Fourier transform-infrared (FT-IR) spectroscopy, field emission-scanning electron microscopy (FE-SEM), energy-dispersive X-ray (EDX) spectroscopy, and transmission electron microscopy (TEM). The isotherm and kinetic studies showed that the data were fitted with Langmuir isotherm and pseudo-second-order kinetic models. The high adsorption capacity of 196 mg g−1 was obtained that indicated a monolayer sorption mechanism. The method was successfully applied for the removal of naproxen from wastewater samples and the removal efficiencies of 84–95% were obtained.